The literary style of Ho Nai Kin’s writings (pdf berbeza) - Goh, Win Nie (2017)
The literary style is a combination of the nature of both creative subject and object, which presented in a perfect written work with distinctive and unique aesthetic pattern. The aesthetic value and significance of literary writing style of an author are the overall style and artistic features of his/her literary works. However, the multiformity between the innate character of an author and his/her scope of action, with the addition of author on different objects have different flexibility and selectivity, lead to the various styles of literary works. Ho Nai Kin (1946-2014) has been writing for more than 50 years, and his poetry and prose have peculiar originality. He is skilled at image capture and understand the natural world, and, through the blending of techniques in terms of rhetoric and representation, creating a poetic essay. His prose and poetry is full of creative imagination and unique expression, which mold his unique literary style, and laid his position in the history of Malaysian Chinese literature. With this in mind, the researcher attempts to investigate the literary style of Ho Nai Kin’s writings, and the scope of research will be the prose and poetry (except science and critical writings) of Ho Nai Kin within the year of 1965 to 2014. By clarifying the creative thinking of Ho Nai Kin via the intrinsic and extrinsic form of his writing, which are the contents and methods of artistic expression of the texts, it provides a better insight on the writer’s writing qualities. On the other hand, identify the value of his prose and poetry.